Investing into the Abyss: The Continued Misclassification of Multi-Sector Managed Funds - Allen, N. (Institutional Knowledge at Singapore Management University, 2010)
The rapid expansion in assets managed by the Australian managed fund industry has resulted in it becoming a major sector of the financial system, second only to that of the banking industry. With more than A$550 billion invested in the industry investors should be concerned about the lack of reliable information available in regard to equity style management. In particular investors should be concerned about the probable mis-match between stated objectives and the actual objectives pursued by fund managers. In this study, we apply return-based style analysis (Sharpe 1988, 1992) to investigate the style and asset allocation strategies of 50 listed managed funds. Using monthly data we investigate manager performance on the basis of the information ratio and adopt a two-step approach following Lobosco and DiBartolomeo (1997) to generate confidence intervals for each of the estimated style weights. A significant contribution made by this paper is that in contrast to Lobosco and DiBartolomeo we initially identified asset classes (on the basis of low correlations and different risk-return measures) and then carried out return based style analysis thus negating the problem of spurious regression. Our findings confer with those of Lobosco and DiBartolomeo and thus suggest that the recommended daily data is not a requirement for constructing reliable style weights. This paper provides further evidence that Sharpe Style weights in conjunction with confidence intervals provide an insight into listed managed funds.